Isolation and detection of low molecular weight cationic peptide in milk of mastitic buffaloes - DEVI, IRUNGBAM KARUNA; GUPTA, SANDEEP KUMAR; SANGHA, S P S; RAMNEEK, RAMNEEK; AHUJA, C S; GUPTA, RENU (The Indian Journal of Animal Sciences, 2012)
Milk samples from mastitic and healthy buffaloes were subjected to centrifugation for preparation of acellular milk. It was subjected to ion exchange chromatography using carboxy methyl resin for purification. The purified protein and peptides obtained by the ion exchange chromatography were subjected to acid urea-polyacrylamide gel electrophoresis using lysozyme as a marker. The milk samples from mastitic buffaloes contained many cationic proteins and peptides. Some of these peptides exhibited migration similar to lysozyme. The SDS-PAGE revealed the presence of low molecular weight peptides in range of 3–5KDa in mastitic milk, whereas these low molecular weight peptides were absent in milk from healthy animals. Tricine SDS PAGE was used for the resolution of peptides using high concentration of Acryl amide (49.5%) for resolving proteins less than 5KDa. It also revealed the presence of low molecular weight peptide of 3–4.5KDa in mastitic milk and absence of such peptides from normal healthy buffalo’s milk. The present work has detected the presence of low molecular weight cationic peptides in milk of mastitic Buffaloes.